Dilematika Gedung Dinas Kebudayaan dan Pariwisata Kota Samarinda dalam Perspektif Pemaknaan Arsitektur dan Fungsionalisme - Utomo, Pandu K.; Dimas Prasojo, Kenan; Sulisthio, Farel; Mahardika, Arya Rizqi Putra (TRANSFORM: Journal of Tropical Architecture and Sustainable Urban Science, 2025)
Public buildings designed as cultural spaces should not only function as symbols of local identity, but also as active and center of cultural activity. This research examines the phenomenon of deviation in the function of space in the building of the Samarinda City Culture and Tourism Office, then analyzes the phenomenon of deviation in function with an approach that focuses on lived experience and perception of the meaning of space. This study founds that there is a lot of space utilization that is not in accordance with its function, reducing the meaning of public architecture as part of a place to interact. The analysis also shows that spaces used for non-cultural activities such as weddings and school events do not represent the cultural emphasis of East Kalimantan. In addition, weak management, the absence of strict space utilization policies, and low community participation confirm that cultural spaces are not sufficiently supported by symbolic design, but must be balanced with consistent and participatory governance. The recommendations are given in the form of revitalization of cultural programs, improving the management system, and optimizing physical design to support the flexibility and sustainability of cultural activities